0687 Bruxism and Sleep Disorder. (27th April 2018) - Han, J
Abstract: Introduction: Sleep bruxism (SB) is reported by 8% of the adult population and is mainly associated with rhythmic masticatory muscle activity (RMMA) characterized by repetitive jaw muscle contractions (3 bursts or more at a frequency of 1 Hz). The purpose of this study was to evaluate the nature of sleep bruxism and to discuss its consequences. Methods: We prospectively studied 20 patients who were referred to the clinical sleep apnea laboratory for study. They underwent standard nocturnal polysomnographic examination; in addition, masticatory activity was measured with a masseter electromyogram. Patients slept in the supine and lateral decubitus positions. Results: Nocturnal clenching was higher in patients with higher respiratory disturbance index. 15 among 20 patients were included in the criteria of obstructive sleep apnea; average respiratory disturbance index (RDI) was 12.7 280 clenches demonstrated in all patients. Conclusion: We conclude that there is an association between sleep related breathing disorder and bruxisms that sleep position affects the incidence of both sleep disordered breathing and bruxisms, and that analysis of apneas and hypopneas and clenching events in both supine and lateral decubitus sleeping positions may be helpful. Support (If Any): Seoul Sleep Center.